Expression of Syndecan 1 on Periodontium treated with Topical Application of Aloe-Vera - Abed, Sabrin Sami; Al-Hijazi, Athra’a Y. (Journal of Baghdad College of Dentistry, 2016)
Background: Periodontium mainly exposed to injury by trauma or pathologic diseases, Aloe vera is a plant has many basic ingredients in its extracted gel that acts as wound healing accelerator in addition to that it’s safe, and economical and without recordable of side effect. This study aimed is to evaluate the effect of topical application of Aloe vera on expression of syndecan -1 by periodontium tissue. Materials and methods: Thirty six male Albino rats were subjected for periodontium defect by electric scaler on the distal sides of both lower anterior teeth. The animals divided into two groups; control group (without treatment) and the experimental group treated with 1ÂµLAloe vera gel/normal saline. Periodontal healing was examined at periods (3, 7, 14 days) for immunohistochemical localization of syndecan 1. Results: Immunohistochemical examination of this study revealed that the aloe vera treatment increase expression of syndecan 1 by epithelial cell, osteoblasts, fibroblast, stromal cells and with highly significant differences in comparison with control and saline. Conclusion: Aloe vera gel may affect the expression of syndecan 1 which seems to play a role in periodontium healing.